Double network nested foam composites with tunable electromagnetic wave absorption performances. Issue 6 (17th May 2019) - Ye, Xinli; Chen, Zhaofeng; Zhang, Junxiong; Wu, Cao; Zhou, Qianbo; Ai, Sufen; Liu, Hezhou; Cui, Sheng
Abstract : A double network nested SiCnw /CF foam composite was fabricated with outstanding absorbing properties. Abstract : A double network nested foam composite with tunable electromagnetic wave absorption performance was fabricated via a carbonization, impregnation, and chemical vapor infiltration method. The research results indicated that the three-dimensional interconnected carbon foam was successfully enhanced by the SiC nanowire network. As expected, the electromagnetic absorption performance of the as-prepared SiC nanowire reinforced carbon foam (SiCnw /CF) was greatly improved by the introduction of the SiC nanowires. The SiCnw /CF composite prepared with a lower concentration of Ni catalyst possessed an excellent microwave absorption property with the lowest reflection loss value of −36.31 dB with a matched thickness of 2.60 mm accompanied by the widest effective bandwidth of 4.52 dB. An increase in catalyst concentration degraded the electromagnetic absorption ability to a certain extent. A potential microwave absorption schematic diagram was finally proposed, and it stated that the SiC nanowire network played an essential role in the improvement of the electromagnetic absorption properties.